Negative partisanship towards the populist radical right and democratic resilience in Western Europe. Issue 5 (4th July 2021) - Meléndez, Carlos; Kaltwasser, Cristóbal Rovira
ABSTRACT: Democracy is under threat today and scholars agree that the main challenge is not sudden regime breakdown, but rather the gradual erosion of key institutions and norms because of growing public support to political forces with illiberal tendencies. In the case of Western Europe, the major threat comes from the populist radical right. Although it is true that the latter has been gaining votes in Western Europe, scholars have not analysed the extent to which a sizeable share of the electorate dislikes this party family. Nevertheless, recent studies reveal that it is important to consider both those who feel close to and those who reject political parties, i.e. positive and negative partisanship. To address this research gap, in this contribution we rely on original survey data for 10 Western European countries to examine negative partisanship towards the populist radical right. The empirical analysis reveals that a large section of the Western European electorate has an aversion to this party family and this finding should be seen as an important sign of democratic resilience. In fact, those who dislike the populist radical right are strong supporters of both democracy per se and the liberal democratic regime.